Heterogeneity in the use of biologics for severe asthma in Europe: a SHARP ERS study - Frix, Anne-Noelle; Heaney, Liam G; Dahlén, Barbro; Mihaltan, Florin; Sergejeva, Svetlana; Popović-Grle, Sanja; Sedlak, Vratislav; Lehtimäki, Lauri; Bourdin, Arnaud; Korn, Stephanie; Zervas, Eleftherios; Csoma, Zsuzsanna; et al. (ERJ open research, 2022)
INTRODUCTION: Treatment with biologics for severe asthma is informed by international and national guidelines and defined by national regulating bodies, but how these drugs are used in real-life is unknown. MATERIALS AND METHODS: The European Respiratory Society (ERS) SHARP Clinical Research Collaboration conducted a three-step survey collecting information on asthma biologics use in Europe. Five geographically distant countries defined the survey questions, focusing on seven end-points: biologics availability and financial issues, prescription and administration modalities, inclusion criteria, continuation criteria, switching biologics, combining biologics and evaluation of corticosteroid toxicity. The survey was then sent to SHARP National Leads of 28 European countries. Finally, selected questions were submitted to a broad group of 263 asthma experts identified by national societies. RESULTS: Availability of biologics varied between countries, with 17 out of 28 countries having all five existing biologics. Authorised prescribers (pulmonologists and other specialists) also differed. In-hospital administration was the preferred deliverance modality. While exacerbation rate was used as an inclusion criterion in all countries, forced expiratory volume in 1 s was used in 46%. Blood eosinophils were an inclusion criterion in all countries for interleukin-5 (IL-5)-targeted and IL-4/IL-13-targeted biologics, with varying thresholds. There were no formally established criteria for continuing biologics. Reduction in exacerbations represented the most important benchmark, followed by improvement in asthma control and quality of life. Only 73% (191 out of 263) of surveyed clinicians assessed their patients for corticosteroid-induced toxicity. CONCLUSION: Our study reveals important heterogeneity in the use of asthma biologics across Europe. To what extent this impacts on clinical outcomes relevant to patients and healthcare services needs further investigation.